3-D tomographic observations of Rossby wave breaking over the North Atlantic during the WISE aircraft campaign in 2017 - Krasauskas, Lukas; Ungermann, Jörn; Preusse, Peter; Friedl-Vallon, Felix; Zahn, Andeas; Ziereis, Helmut; Rolf, Christian; Plöger, Felix; Konopka, Paul; Vogel, Bärbel; Riese, Martin (Atmospheric Chemistry and Physics, 2021)
This paper presents measurements of ozone, wa-ter vapour and nitric acid (HNO3) in the upper tropo-sphere/lower stratosphere (UTLS) over North Atlantic andEurope. The measurements were acquired with the Gim-balled Limb Observer for Radiance Imaging of the At-mosphere (GLORIA) during the Wave Driven IsentropicExchange (WISE) campaign in October 2017. GLORIAis an airborne limb imager capable of acquiring both 2-D data sets (curtains along the flight path) and, whenthe carrier aircraft is flying around the observed air mass,spatially highly resolved 3-D tomographic data. Here, wepresent a case study of a Rossby wave (RW) breakingevent observed during two subsequent flights 2 d apart. RWbreaking is known to steepen tracer gradients and facili-tate stratosphere–troposphere exchange (STE). Our measure-ments reveal complex spatial structures in stratospheric trac-ers (ozone and nitric acid) with multiple vertically stacked fil-aments. Backward-trajectory analysis is used to demonstratethat these features are related to several previous Rossbywave breaking events and that the small-scale structure ofthe UTLS in the Rossby wave breaking region, which is oth-erwise very hard to observe, can be understood as stirringand mixing of air masses of tropospheric and stratosphericorigin. It is also shown that a strong nitric acid enhancementobserved just above the tropopause is likely a result of NOxproduction by lightning activity. The measurements showedsignatures of enhanced mixing between stratospheric and tro-pospheric air near the polar jet with some transport of watervapour into the stratosphere. Some of the air masses seen in3-D data were encountered again 2 d later, stretched to verythin filament (horizontal thickness down to 30 km at some al-titudes) rich in stratospheric tracers. This repeated measure-ment allowed us to directly observe and analyse the progressof mixing processes in a thin filament over 2 d. Our resultsprovide direct insight into small-scale dynamics of the UTLSin the Rossby wave breaking region, which ...